Palaeolithic handaxes in Scotland - Saville, Alan; O'Neil, Marion (Proceedings of the Society of Antiquaries of Scotland, 1998)
The occurrence and typology of artefacts of handaxe type in Scotland are reviewed and it is concluded that, though some are genuine Lower Palaeolithic implements, none of these finds provides convincing evidence for Early Palaeolithic human presence in Scotland.